Efeito da exposição à oxigenação hiperbárica na expressão de KI - 67, PCNA e VEGF no polo inferior do baço de ratos submetidos à esplenectomia subtotal - Marcela Souza Lima Paulo (2015)
Purpose: To evaluate whether hyperbaric oxygen increases cell proliferation by expression of Ki67 and PCNA and vascular proliferation by expression of VEGF in the inferior pole of the spleen after subtotal splenectomy. To verify whether there is a correlation between the size of the inferior pole of the spleen and the amount of positive cells for the markers Ki67, PCNA and VEGF. Methods: Forty male Wistar rats, weighing 358.9g ± 34.8 underwent subtotal splenectomy with the preservation of the inferior pole and divided into two groups: group A (n=20)without hyperbaric oxygenation; group B (n=20)submitted to hyperbaric oxygenation. Groups A and B were divided into two subgroups of 10 animals each, according to the time of euthanasia: subgroup of 15 days, subgroup of 45 days. The animals were weighed on the day of subtotal splenectomy, on the 10th day and the day of euthanasia. The inferior pole of the spleen was measured in length, width and thickness on the day of subtotal splenectomy and on the day of euthanasia (15th and 45th days). After removal, the inferior pole of the spleen was weighed and fixed in formalin and processed in paraffin for immunohistochemical analysis using markers of cell proliferation (Ki67 and PCNA) and vascular (VEGF). Results: All animals survived until euthanasia. There was an increase animal weight of all subgroups from the beginning to the end of the experiment. The length, width and thickness of the inferior pole of the spleen did not change in either group. Immunohistochemical analysis showed that in group A, the animals from the subgroup of 45 days without hyperbaric oxygen showed a significant increase of Ki67 positive cells compared to subgroup of 15 days (p=0.001). The animals in group B showed higher Ki67 immunostaining that the subgroups without HBO (p<0.05). The expression of PCNA in groups A and B was greater in animals from the subgroup of 45 days when compared to the subgroup of 15 days (p<0.05). The animals of subgroup B15 undergoing hyperbaric oxygenation showed higher immunopositivity than subgroup A15 without HBO (p=0.0029). In group B, animals with hyperbaric oxygenation, there was a significant correlation between the width of the inferior pole of the spleen and cell proliferation by PCNA in subgroup B15 (p=0.048) and significant correlation was observed between the length of the inferior pole of the spleen and the cell proliferation by PCNA in subgroup B45. VEGF was not significant (p>0.05) between the subgroups, however, in the subgroup B45, there was a significant correlation between the expression of VEGF and the size of the inferior pole of the spleen (p=0.004). Conclusions: The hyperbaric oxygenation after subtotal splenectomy, increased cell proliferation by the expression of Ki67 and PCNA and did not increase vascular proliferation by the expression of VEGF in the inferior pole of the spleen. In animals submitted to hyperbaric oxygenation there was a relationship between the size of the inferior pole of the spleen and the amount of cells positive for PCNA and VEGF, but this relationship was not found for Ki67.